Systems level analysis of protein synthesis patterns associated with bacterial growth and metabolic transitions - Vohradsky, Jiri; Thompson, Charles J (Proteomics, 2006)
Gene expression databases, acquired by proteomics and transcriptomics, describe physiological and developmental programs at the systems level. Here we analyze proteosynthetic profiles in a bacterium undergoing defined metabolic changes. Streptomyces coelicolor cultured in a defined liquid medium displays four distinct patterns of gene expression associated with growth on glutamate, diauxic transition, and growth on maltose and ammonia that terminates by starvation for nitrogen and entry into stationary phase. Principal component and fuzzy cluster analyses of the proteome database of 935 protein spot profiles revealed principal kinetic patterns. Online linkage of the proteome database (SWICZ) to a protein-function database (KEGG) revealed limited correlations between expression profiles and metabolic pathway activities. Proteins belonging to principal metabolic pathways defined characteristic kinetic profiles correlated with the physiological state of the culture. These analyses supported the concept that metabolic flux was regulated not by individual enzymes but rather by groups of enzymes whose synthesis responded to changes in nutritional conditions. Higher-level regulation is reflected by the distribution of all kinetic profiles into only nine groups. The observation that enzymes representing principal metabolic pathways displayed their own distinctive average kinetic profiles suggested that expression of a "high-flux backbone" may dominate regulation of metabolic flux.
Keywords: Streptomyces coelicolor; signální transdukce; proteom; Signal Transduction; 2D gelová elektroforéza; Nitrogen; dusík; Adaptation, Physiological; Glutamic Acid; sladidla; maltosa; Ammonia; bakteriální proteiny; regulace genové exprese u bakterií; proteosyntéza; Protein Array Analysis; čipová analýza proteinů; Sulfur Radioisotopes; Electrophoresis, Gel, Two-Dimensional; Gene Expression Regulation, Bacterial; Bacterial Proteins; fyziologická adaptace; Maltose; Sweetening Agents; Proteome; methionin; Methionine; Protein Biosynthesis; radioizotopy síry; amoniak; kyselina glutamová